2005
DOI: 10.1074/jbc.m413733200
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression, Purification, and Characterization of Recombinant Rat Cysteine Dioxygenase

Abstract: Cysteine dioxygenase (CDO, EC 1.13.11.20) catalyzes the oxidation of cysteine to cysteine sulfinic acid, which is the first major step in cysteine catabolism in mammalian tissues. Rat liver CDO was cloned and expressed in Escherichia coli as a 26.8-kDa N-terminal fusion protein bearing a polyhistidine tag. Purification by immobilized metal affinity chromatography yielded homogeneous protein, which was catalytically active even in the absence of the secondary protein-A, which has been reported to be essential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 32 publications
9
72
0
Order By: Relevance
“…Our inductively coupled plasma mass spectroscopy analysis of purified recombinant wild-type human CDO yielded an iron incorporation of ϳ68%, which is much higher than 10% or 25% reported by other groups (18,19,31,35). Besides iron, other metal elements were detected in purified recombinant CDO, including zinc (18.1%) and trace amounts of magnesium (0.41%) and manganese (0.25%) (Fig.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Our inductively coupled plasma mass spectroscopy analysis of purified recombinant wild-type human CDO yielded an iron incorporation of ϳ68%, which is much higher than 10% or 25% reported by other groups (18,19,31,35). Besides iron, other metal elements were detected in purified recombinant CDO, including zinc (18.1%) and trace amounts of magnesium (0.41%) and manganese (0.25%) (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…4C). We determined a K m of 3.1 Ϯ 0.3 mM with a k cat of 1.7 s Ϫ1 that is remarkably higher than the k cat for mouse CDO (0.06 s Ϫ1 ) or rat CDO (0.72 s Ϫ1 ) reported previously (18,31,35).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We previously showed that DL-homocysteine binds to the active site of rat CDO (57). However, the reported extent of inhibition of mammalian CDOs by homocysteine remains ambiguous (17,19,25), and very inefficient use of homocysteine as a substrate has recently been reported (80). Comparable inhibition by cysteamine has been reported for other bacterial CDOs (21).…”
Section: Resultsmentioning
confidence: 94%
“…CDO, for instance, requires ferrous iron for activity (6 -8). Moreover, because of issues with very low iron occupancy (Ͻ10 -25%) after aerobic purification of the enzyme, ferrous iron must be added to assays of CDO to achieve full activity (7,13). Because ADO is also a cupin protein, we wanted to test whether it binds a transition metal and, if so, whether it is required for catalytic activity.…”
Section: Characterization Of Metal Binding and Its Contribution To Camentioning
confidence: 99%